Biomechanical investigation of dental implant using resonance frequency analysis, 3D bone assessment and finite element analysis - Genisa, Maya (2018)
Biocompatibility and biomechanics assessment after implant placement become an essential task to support longevity of dental implant. Understanding the factors that supporting bony osseointegration, stability of implant and characteristic of new biomechanics system of dental implant are needed. Therefore, the behavior of dynamic properties such as stress propagation and micromotion as responses of different loading including pre and post crown condition can be estimated. However, in current clinical technology, the biomechanical behavior of dental implant is still unpredicted because of unavailability of the instrument to measure those phenomena clinically. A 3D imaging technology such as Cone Beam Computed Tomography (CBCT) able to produce better image of implant dental system and gives some advantages. However, some issues are still embedded in their application especially for bone density assessment. The objective of this research is to assess a dental implant biomechanically in three dimensions (3D), which include the examination on accuracy and repeatability of CBCT, monitoring of implant stability using Resonance Frequency Analysis (RFA) and its correlation with the bone quality and quantity and changes of density during dental implant treatment. Futher objectives are to investigate the effect of loading and variables on stress distribution and micro motion of dental implant system in pre and post crown condition based on numerical study through Finite Element Analysis (FEA) on model and in vivo data. Methodology of the research was set to achieve the entire objectives which involved 10 implant patientsand an oral surgeon at Hospital USM (HUSM) during implant treatment. Monitoring of their implant progress were conducted in three stages: immediate after implant placement, 3 months after implant surgery, and 4 months after implant placement or 1 month after crown installation. Statistical analyses were performed in SPSS software, while the Finite Element Analysis (FEA) studies were conducted by using ANSYS Workbench software to simulate the generated stress distribution and micromotion due to different loading (vertical, horizontal and removal torque loading) for pre and post crown condition. The preparation of FEA study including the segmentation and meshing were conducted on MIMICS and 3-Matic software based on CBCT image. The result showed that the cortical thickness and bone height had higher correlation coefficient with implant stability compared to density and width of bone. Bone resorption during healing stage occurred within 3 months after surgery, osseointegration or remodeling occurred 4 months after surgery and implant stability increases significantly 4 months after surgery. The stresses generated during loading simulation was low in the patient with high and moderate implant stability and high for patient with low implant stability. The higher generated stress tends to produce higher micromotion. Stress and micro motion are two crucial factors that determine the implant stability, osseointegration and remodeling activity.